Eco-friendly polymer-based nanocomposites for pharmaceutical applications - Muhamad, I. I. (wiley, 2015)
Interest in eco-friendly polymeric materials is growing due to concerns over increasing carbon emission and the limited nature of petroleum and natural gas resources. These eco-friendly polymers, either natural or synthetic, can be biodegradable and nontoxic. However, they possess some inherent limitations such as poor mechanical properties, low melt viscosity, high gas and vapor permeability and low heat distortion temperature, which restrict their use for a wide range of applications. Therefore, modifications are needed to make them suitable for targeted applications. One of the interesting strategies is by the incorporation of second phase nanoscale component into the biopolymers to produce a new eco-friendly nanocomposite material with new and improved properties. Nanocomposites are novel materials with drastically improved properties due to the incorporation of small amounts (< 5 wt%) of nano-sized fillers, such as clays, carbon nanostructures and metals, into a polymer matrix. Currently eco-friendly polymer-based nanocomposites are widely used in pharmaceutical and biomedical applications due to their unique properties, such as specific physical strength and large surface area to volume ratio and physiochemical properties, which modify the normal biological activity. This chapter will focus on eco-friendly polymers and eco-friendly polymer nanocomposites in pharmaceutical and biomedical applications such as drug delivery system, tissue engineering and biosensor. In addition, this chapter also focuses on carrageenan-based nanocomposite in drug delivery system.